Safer cycling in older age (SiFAr): effects of a multi-component cycle training. a randomized controlled trial - Keppner, Veronika; Krumpoch, Sebastian; Kob, Robert; Rappl, Anja; Sieber, Cornel; Freiberger, Ellen; Siebentritt, Hanna (BMC Geriatrics, 2023)
Background: The risk of older adults being injured or killed in a bicycle accident increases significantly due to the age-related decline of physical function. Therefore, targeted interventions for older adults to improve safe cycling competence (CC) are urgently needed. Methods: The “Safer Cycling in Older Age” (SiFAr) randomized controlled trial investigated if a progressive multi-component training program related to cycling improves CC of older adults. Between June 2020 and May 2022, 127 community-dwelling persons living in the area Nürnberg-Fürth-Erlangen, Germany aged 65 years and older were recruited, who are either (1) beginners with the e-bike or (2) feeling self-reported unsteadiness when cycling or (3) uptaking cycling after a longer break. Participants were either randomized 1:1 to an intervention group (IG; cycling exercise program, 8 sessions within 3 months) or an active control group (aCG; health recommendations). The CC as primary outcome was tested not blinded in a standardized cycle course prior and after the intervention period and after 6–9 months, which consists of variant tasks requiring skills related to daily traffic situations. Regression analyses with difference of errors in the cycling course as dependent variable and group as independent variable adjusted for covariates (gender, number of errors at baseline, bicycle type, age and cycled distance) were performed. Results: 96 participants (73.4 ± 5.1 years; 59.4% female) were analyzed for primary outcome. Compared to the aCG (n = 49), the IG (n = 47) made an average of 2.37 fewer errors in the cycle course after the 3 months intervention period (p = 0.004). People with more errors at baseline had higher potential for improvement (B=-0.38; p < 0.001). Women on average made 2.31 (p = 0.016) more errors than men, even after intervention. All other confounders had no significant effect on the difference in errors. The intervention effect was very stable until 6–9 months after the intervention (B=-3.07, p = 0.003), but decreased with a higher age at baseline in the adjusted model (B = 0.21, p = 0.0499). Conclusion: The SiFAr program increases cycling skills among older adults with self-perceived needs for improvement in CC and could easily be made available to a broad public due to its standardized structure and a train-the-trainer approach. Trial Registration: This study was registered with clinicaltrials.gov: NCT04362514 (27/04/2020), https://clinicaltrials.gov/ct2/show/NCT04362514.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Aging; Cycle training; Cycling safety; e-bike; Mobility; Randomized controlled trial